IMPROVING STUDENTS’ CRITICAL AND COLLABORATIVE THINKING SKILLS THROUGH THE THINK-PAIR-SHARE MODEL IN PANCASILA EDUCATION AT THE FOURTH GRADE OF ELEMENTARY SCHOOL - Dewi Septiani (International Journal of Multidisciplinary Reseach, 2026)
This study was motivated by the condition of Pancasila Education learning at SD Al-Qur’an Islamiyah, which is still predominantly teacher-centered through lecture methods, resulting in students’ critical and collaborative thinking skills not being optimally developed. The Think-Pair-Share (TPS) learning model was selected as an innovative solution that provides opportunities for students to think independently, engage in pair discussions, and share ideas in front of the class. This Penelitian Tindakan Kelas (PTK) employing the Kemmis and McTaggart model, was conducted in two cycles to improve the critical thinking patterns and collaborative skills of fourth-grade students. The results of observations in Cycle I indicated that students’ critical thinking skills were in the “good” category with an average score of 76%; however, their evaluation skills still required improvement. Meanwhile, collaborative skills in Cycle I were categorized as “fair,” with an average percentage of 56.21%, where students began to participate actively but had not yet contributed and taken responsibility evenly. After improvements in instructional strategies and the enrichment of learning media, Cycle II showed significant progress. Students’ critical thinking skills increased to the “very good” category with an average score of 88.5%, while collaborative skills improved to “good” to “very good” levels, with an average of 80.80%. Student interactions during discussions became more active and balanced, and they demonstrated the ability to respect differences and work collaboratively with a sense of responsibility. This study confirms that the Think-Pair-Share model is effective in developing students’ critical thinking and collaborative skills, while also enhancing their self-confidence and understanding of Pancasila values through a more interactive and meaningful learning process. These findings can serve as a reference for teachers and schools in improving Pancasila Education practices and open opportunities for further research.